CMET promotes metastasis and epithelial‐mesenchymal transition in colorectal carcinoma by repressing RKIP. Issue 5 (5th November 2020) - Wang, Siyun; Ma, Haiqing; Yan, Yan; Chen, Yu; Fu, Sirui; Wang, Junjiang; Wang, Ying; Chen, Hao; Liu, Jianhua
Abstract: Increasing evidence indicates that c‐mesenchymal‐epithelial transition factor (cMET) plays an important role in the malignant progression of colorectal cancer (CRC). However, the underlying mechanism is not fully understood. As a metastasis suppressor, raf kinase inhibitory protein (RKIP) loss has been reported in many cancer types. In this study, the expression levels of cMET and RKIP in CRC tissues and cell lines were determined, and their crosstalk and potential biological effects were explored in vitro and in vivo. Our results showed that cMET was inversely correlated with RKIP. Both cMET upregulation and RKIP downregulation indicated poor clinical outcomes. Moreover, the MAPK/ERK signaling pathway was implicated in the regulation of cMET and RKIP. Overexpression of cMET promoted tumor cell epithelial‐mesenchymal transition, invasion, migration, and chemoresistance, whereas the effects could be efficiently inhibited by increased RKIP. Notably, small hairpin RNA‐mediated cMET knockdown dramatically suppressed cell proliferation, although no RKIP‐induced influence on cell growth was observed in CRC. Altogether, cMET overexpression may contribute to tumor progression by inhibiting the antioncogene RKIP, providing preclinical justification for targeting RKIP to treat cMET‐induced metastasis of CRC. Abstract : We observed for the first time the expression and clinical significance of c‐mesenchymal‐epithelial transition factor (cMET) were opposite to those of raf kinase inhibitory protein (RKIP) in colorectal cancer (CRC) tissues and cell lines. Second, we illustrated that cMET regulated RKIP expression by activating the downstream MAPK/ERK signaling pathway. Additionally, in vitro and in vivo experimental results demonstrated that RKIP acted as a potential target for tumor metastasis driven by cMET in CRC.